Using Probabilistic Models to Appraise and Decide on Sovereign Disaster Risk Financing and Insurance - Ley-Borrás, Roberto (World Bank, Washington, DC, 2015)
This paper presents an overview of the structure of probabilistic catastrophe risk models, discusses their importance for appraising sovereign disaster risk financing and insurance instruments and strategy, and puts forward a model and a process for improving decision making on the linked disaster risk management strategy and sovereign disaster risk financing and insurance strategy. The paper discusses governments use of probabilistic catastrophe models to inform sovereign disaster risk financing decision making and describes the ex ante and ex post financing instruments available for responding to extreme natural events. It also discusses the challenge of appraising sovereign disaster risk financing and insurance instruments, including a review of the multiple dimensions of disaster risks and the value that probabilistic catastrophe risk models provide. The decision making framework for sovereign disaster risk financing and insurance put forward by the paper includes the use of a decision model (an influence diagram) as a rigorous representation of the relationships between the decisions, uncertain events, and consequences relevant to sovereign disaster risk financing and insurance decision making. The framework also includes a process for generating high-quality customized components for the decision model, and a tool for designing coherent sovereign disaster risk financing and insurance strategies. The paper ends with suggestions for improving catastrophe risk models to facilitate sovereign disaster risk financing and insurance decision making.